Estudo fitoquímico e atividades leishmanicida e antioxidante de Aspidosperma pyrifolium Mart. (Apocynaceae) - Barbosa, Daniel Porto (2014)
The species of the genus are Aspidosperma trees with a wide variety of sizes and growing in different habitats, are distributed throughout the Americas, and in Brazil cataloged about 50 species of this genus. The species A. pyrifolium is a tree found in the caatinga of Brazil, popularly known as pereiro, pereiro-white, pereiro-black, mahogany pink clover pereiro-of-skirt and pereiro-the-wild. From this species were isolated some alkaloids and evaluated cardiovascular activities, antioxidant and insecticide. Given the scarcity of studies on this species in the literature and the great chemical and pharmacological potential of species of Aspidosperma gender, a phytochemical study of the species A. pyrifolium in order to contribute to the knowledge of the chemical and pharmacological potential of the species was carried out and the genre, and to measure leishmanicide and antioxidant activities. Was conducted chemical and evaluation of leishmanicide activity of hexane and methanol extracts of the leaves. The plant material was subjected to trituration with hexane and then with methanol to obtain the crude extract. Then the material is subjected to successive separation processes using classical chromatography column and liquid chromatography and medium pressure identify the substance was found possible by spectroscopic NMR (Nuclear Magnetic Resonance). Were isolated triterpene betulinic acid and benzoic acid, was identified by the presence of alkaloids. The antioxidant activity was performed according to the methods of total phenolic and ABTS and results demonstrate the ability antioxidade the raw extracts and fractions. With respect to the leishmanicidal activity promastigotes of L. amazonesis strains were used in the in vitro assay incubated for 24 hours. After this period, cell viability was determined by testing MTT reduction of tetrazolium salt. The results showed that four fractions resulting from the phytochemical fractionation showed leishmanicide ativadade, including the two compounds isolated betulínco the acid and benzoic acid.